Extensive rectus sheath hematoma secondary to erroneous technique of anticoagulant injection - Hassan S,; Kosai NR,; Reynu Rajan,; Shuhaili MA,; Sutton PA,; DC, Smith (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Rectus sheath hematoma (RSH) is a rare clinical entity that has been associated with the use of injectable anticoagulant therapy. Although low molecular weight heparin (LMWH) was proven to have a better safety profile than its predecessor, it is not without its own risk of bleeding. The increase in use of self-injectable LMWH in both in-patient as well as out-patient basis warrants greater awareness among health care providers, patients and caregivers regarding the potential risks and identification of possible complications. We present a fatal case of rectus sheath hematoma in an elderly man that occurred following erroneous technique of Dalteparin injection.